Gamma Decay Hindrance Factors Used in Systematic Configuration Assignments (Письма в ЭЧАЯ, 2024)
A simple empirical relation is proposed to correlate the K-hindrance factor with the number of quasiparticles in the state configuration. The reduced hindrance $F_{ u}$ = $({t_{1/2}^{γ}}/{t_{1/2}^{w}})^{1/ u}$ has been empirically modified such that $ u$= $Δ K-L-(N_{π}-N_{ u})$, instead of { ormalsize $ u$} = $Δ K-L$ where $N_{ u}$ and { ormalsize $N_{π}$} are the numbers of neutron and proton quasiparticles in the state configuration. In systematics, the modified hindrance factor can be used to uniquely determine the $K$-isomer state configuration.